1971
DOI: 10.1530/acta.0.0680079
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic Receptors in Human Benign Nodular Prostatic Hyperplasia

Abstract: Following incubation of slices from benign nodular prostatic hyperplasia (BNPH) with [3H] testosterone in vitro, a selective accumulation and retention of radioactivity was found in the prostatic tissue. The uptake and retention of androgen by the pyramidalis muscles was significantly lower. The 105 000 \m=x\ g supernatant fraction of homogenates obtained from BNPH contained androphilic macromolecules excluded from Sephadex G-100 gel, both after incubation of the slices from [3H] testosterone and [3H] 5\g=a\-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…Steins et al(1974) reported that the binding rate with dihydrotestosterone of glandular type of the hypertrophic prostate was higher than that of the poor glandular type. In the present study, the proportion of glandular constituent in hypertrophic prostates was not correlated with binding affinity to dihydrotestosterone, and this might be due to the disparity of histological (Tveter, 1971;Shimazaki et al, 1972;Nozu and Tamaoki, 1975), and the present experiments also confirmed these results. Sch 13521 was a potent anti-androgen (Neri et al, 1972), but its mechanism of action was still disputable.…”
Section: Binding Capacity Of Acetone-dried Cytosolsupporting
confidence: 80%
See 1 more Smart Citation
“…Steins et al(1974) reported that the binding rate with dihydrotestosterone of glandular type of the hypertrophic prostate was higher than that of the poor glandular type. In the present study, the proportion of glandular constituent in hypertrophic prostates was not correlated with binding affinity to dihydrotestosterone, and this might be due to the disparity of histological (Tveter, 1971;Shimazaki et al, 1972;Nozu and Tamaoki, 1975), and the present experiments also confirmed these results. Sch 13521 was a potent anti-androgen (Neri et al, 1972), but its mechanism of action was still disputable.…”
Section: Binding Capacity Of Acetone-dried Cytosolsupporting
confidence: 80%
“…Characteristics of receptors and transfer of androgen receptor complexes into nuclei were widely investigated in recent years (reviewed by Liao et al, 1974b). It was also observed that human prostatic tissues contained specific protein which binds to testosterone and dihydrotestosterone in high affinity fashion (Hansson et al, 1971;Reed and Stitch, 1973;Fraser et al, 1974 …”
mentioning
confidence: 99%
“…Epithelial tissue actively metabolized androstenedione, and the conversion of testosterone to 5a-dihydrotestosterone was greater than in the fibro-muscular tissue. This is in accord with the results of Hansson and colleagues (Hansson, Tveter, Attramadal & Torgersen, 1971) who found a pronounced uptake of [3H]testosterone into benign nodular prostatic tissue with a significantly lower accumulation in the muscular tissue. Becker, Kaufmann, Kloster¬ halfen & Voigt (1972) also noted a difference in the uptake and metabolism of testo¬ sterone in adenomatous benign hypertrophy specimens compared with samples composed mainly of fibrous tissue.…”
Section: In-vitro Studiessupporting
confidence: 93%
“…The incorporation of thymidine into DNA was most rapid on the third day in culture. The timing of the uptake peak was reminiscent of that found in the rat prostate remnant after hemiprostatectomy, where during the repair process a similar metaplasia through a " malignant-looking " epithelial pattern was noted in the prostatic cavity (Feminella et al, 1971 (Huggins, 1947) (British Medical Journal, 1971), BPH displays biochemical properties which are characteristic of an androgen-dependent tissue: it is able to convert testosterone to the active androgen, 5az-dihydrotestosterone (Siiteri and Wilson, 1970) and possesses androgen-specific receptor proteins (Hansson et al, 1971) thought necessary for the retention and intracellular transport of hormones. However, despite the fact that prostatic carcinoma responds to testosterone under the culture conditions used in the present work (McMahon,Butler and Thomas,333 1972), no morphological change was seen with BPH (Table I).…”
Section: Effects Of Hormnonesmentioning
confidence: 93%